2019
DOI: 10.4073/csr.2019.3
|View full text |Cite
|
Sign up to set email alerts
|

Individualized funding interventions to improve health and social care outcomes for people with a disability: A mixed‐methods systematic review

Abstract: 1 | PLAIN LANGUAGE SUMMARY 1.1 | Individualized funding has positive effects on health and social care outcomes Individualized funding provides personal budgets for people with disabilities, to increase independence and quality of life. The approach has consistently positive effects on overall satisfaction, with some evidence also of improvements in quality of life and sense of security. There may also be fewer adverse effects. Despite implementation challenges, recipients generally prefer this intervention to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 231 publications
2
42
0
Order By: Relevance
“…Organizations will be forced to either withdraw from the scheme due to financial pressures or abandon the additional, unfunded work that may place more burden on remaining providers, or on families who are left with nowhere to turn if this administrative burden is not picked up by government or advocacy organizations. It is worth noting that growth in administrative burdens has been a feature of personalization schemes internationally (Fleming et al, 2019). Generally, these have been attributed to the design of overly complex systems that have emerged naturally out of poor design and could therefore be corrected through redesign (Fleming et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Organizations will be forced to either withdraw from the scheme due to financial pressures or abandon the additional, unfunded work that may place more burden on remaining providers, or on families who are left with nowhere to turn if this administrative burden is not picked up by government or advocacy organizations. It is worth noting that growth in administrative burdens has been a feature of personalization schemes internationally (Fleming et al, 2019). Generally, these have been attributed to the design of overly complex systems that have emerged naturally out of poor design and could therefore be corrected through redesign (Fleming et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that growth in administrative burdens has been a feature of personalization schemes internationally (Fleming et al, 2019). Generally, these have been attributed to the design of overly complex systems that have emerged naturally out of poor design and could therefore be corrected through redesign (Fleming et al, 2019). However, there may be deeper drivers worth investigating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas many service users may have been deterred by the relative unattractiveness of previous systems, improved choice and direction in decision-making may increase demand. A systematic review of research on the effectiveness of individualised funding schemes across several countries has found that fears in relation to the overwhelming of the social care system's capacity due to an introduction of individualised funding are not supported by evidence (Fleming et al, 2019). However, it has been pointed out that, as demand for social protection begins to exceed budgetary limitations, governments face an inevitable trade-off between the coverage and the generosity of the support system.…”
Section: Development Of Individualised Funding Schemesmentioning
confidence: 99%
“…Recently, an international shift from traditional, group-disability supports toward individualised funding has occurred (Fleming et al 2019). In Australia, a government funded individual disability package known as the National Disability Insurance Scheme (NDIS) was progressively implemented from 2016.…”
Section: Introductionmentioning
confidence: 99%